Association of Patient-Reported Care Coordination With Patient Satisfaction. Issue 1 (January 2015) - Wang, Margaret C.; Mosen, David; Shuster, Elizabeth; Bellows, Jim
<x xml:space="preserve">Abstract</x> Little is known about the relationship between care coordination directly assessed from the patient's perspective and patient satisfaction. This study applied multiple logistic regression models to examine associations between patient-reported care coordination and patient satisfaction among 1367 patients with diabetes. We found robust positive relationship between care coordination and patient satisfaction with overall chronic care (odds ratio [OR] = 1.78), one's regular doctor (OR = 1.85), and the way care was organized (OR = 1.98). Implications for health plans, providers, and future research are discussed.